P2-S8.05 Use of cellular telephones in a study of high-risk patients. (10th July 2011) - Craig, D; Hensel, D; Fortenberry, J D; Harezlak, J; Jones, K
Abstract : Objectives: To describe interest, uptake, advantages and problems associated with the use of cellular phones in a study of incident STDs in a high-risk population. Methods: Study participants (SP) (N=357; 18–29 yrs; 91% African American; 19.9% incident STD at enrolment: Chlamydia, Gonorrhoea and Trichomoniasis) were enrolled in a 12-week study involving weekly STD sampling and three times daily electronic diary submission via cellular phone. SPs received 3 months of free unlimited calling, texting and internet browsing as part of study and an option to retain the phone at study conclusion. Results: Eligible SPs, the majority of whom were self-referred, were placed on a waiting list (volume range: 50–150 people) until space in the study was available (avg time: 4 months). About 50% of persons on the waiting list were not enrolled; common barriers included invalid contact information and no call back. Advantages to SP cell phone use included: paperless data collection (SPs who completed the study [N=261] submitted 89.99% of expected diaries), facilitated communication between SP and study staff, free cell minutes/texting and internet, and the option to keep phone at study conclusion (about 80%) as incentives to SPs. Challenges with cell phone use included issues with actual use (most common: failing to charge phone or poor care of phone), technical problems (most common: equipment failure [11.2%] and connectivity problems [21.1%]), theft (about 10%) and equipment breakage/damage [14.8%]). Once SP reported equipment issues, the time to replacement was short (average: 2 days). Conclusion: The data support the feasibility of using cellular phones in a high-risk population. Participants were not recruited for the waiting list, but self-referred. SPs were able to complete and submit surveys correctly and work with technical issues encountered.